Banjar Economic Platform (BEP) Model: Integrating Local Wisdom into Digital Economic Literacy in Economic Learning - Muhammad Rahmatullah; Edy Suryanto; Ananda Setiawan; Dwi Atmono; Alfi Fadhilah Hakim Hrp; Rizal Iskandar; Okta Selik Ramadhan; Hafid Febriansyah (Gawi: Journal of Action Research, 2026)
Economic literacy among high school students remains critically low, as evidenced by test scores falling far below national and regional expectations in South Kalimantan. This issue stems from abstract, non-contextual learning models and globalization, which gradually erodes traditional local economic wisdom. This study aims to develop and describe the design of the Banjar Economic Platform (BEP), an integrated digital platform that documents the Banjar economic lexicon and serves as a culturally responsive economics learning resource. Adopting a Research and Development (R&D) methodology guided by the ADDIE model, this study involved 35 purposively selected participants, including native Banjar speakers (N=3), media and subject matter experts (N=4), and high school economics teachers (N=28). Data were collected via semi-structured interviews and structured questionnaires, then analyzed using a sequential mixed-methods approach. The needs analysis revealed that incorporating the Banjar economic lexicon (e.g., bajajak, basawah, maadati, baulah, basambat, and maulah) is highly relevant for making abstract economic concepts meaningful. Expert media validation yielded an overall Aiken’s V coefficient of 0.89, falling into the "Very High" validity category. Furthermore, functional evaluation through black-box testing demonstrated a 100% success rate across all critical system features and operational workflows. The BEP offers a practical, culturally responsive framework that bridges modern economic theory with traditional practices. It serves as a novel educational model that operationalizes ethnolinguistic preservation to foster sustainable economic literacy and safeguard cultural identity in the digital era.